Sensitivity analysis of variables influencing temperature warping stresses in hydraulic concrete slabs (2009)
The sensitivity analysis of each of the variables that influence the calculation of the warping stresses produced by the temperature difference of the faces of the hydraulic concrete slab is presented. The variables analyzed were: the modulus of elasticity of the concrete, the coefficient of expansion of the concrete, the temperature difference between the faces of the slab, the thickness of the concrete slab, the Poisson's ratio of the concrete, the modulus of reaction of the slab support, the length of the slab and the width of the concrete slab. Through the sensitivity analysis it is possible to define the degree of importance of the variables and identify the most sensitive ones, or those that affect to a greater or lesser degree the mechanical behavior of concrete slabs due to the effect of temperature changes, in order to have tools that allow pavement design engineers to be certain of the variables that must be modified to ensure that the structural model meets the design requirements and ensures good mechanical behavior of the slab throughout its service life.